Development of fetal thymocytes in organ cultures. Effect of interleukin 2 (The Rockefeller University Press, 1987)
Most fetal thymocytes from 14-d mouse embryos are Thy-1+, L3T4-, Ly-2-, and express the receptor for interleukin 2 (IL-2). The development of thymocytes has been followed in fetal thymus organ cultures. When fetal thymus from 14-d embryos were cultured for a 6-d period, thymocytes increased in number 20-40-fold, and 95% became Thy-1+, L3T4+, Ly-2+. The addition of IL-2 to organ cultures of 14-d fetal thymus inhibited, in a dose-dependent manner, cell proliferation and the appearance of Thy-1+, L3T4+, Ly-2+ thymocytes. The addition of IL-2 also resulted in the appearance of a population of cells that were cytotoxic for syngeneic and allogeneic fetal thymocytes and syngeneic tumour targets. While the events that lead to the expression of the IL-2 receptor on 14- d fetal thymocytes are unknown, IL-2 in fetal thymus organ cultures inhibits the normal maturation of fetal thymocytes and raises the question of whether the cytotoxic cells that appear reflect selection through an alternative pathway of development.